Influence of Capital Structure on the Performance of Nepalese Insurance Companies - Ram Sagar Yadav,; Silwal, Raman; Kilambu, Rasish; Shah , Ritika Kumar; Khadka, Rohit (Nepalese Journal of Economics, 2024)
This study examines the influence of capital structure on the performance of Nepalese insurance companies. Return on assets and earnings per share are selected as the dependent variables. The selected independent variables are total debt ratio, total equity to total assets, leverage, assets tangibility, firm size and liquidity ratio. The study is based on secondary data of 17 insurance companies with 102 observations for the study period from 2016/17 to 2021/22. The data were collected from publications and websites of insurance companies and annual reports of the selected insurance companies. The correlation coefficients and regression models are estimated to test the significance and importance of capital structure on the performance of Nepalese insurance companies. The study showed that total debt ratio has a positive impact on return on assets. It means that higher the total debt to total equity ratio, higher would be the return on assets. Similarly, total equity to total assets ratio has a positive impact on return on assets. It means that increase in total equity to total assets ratio leads to increase in return on assets. Likewise, leverage has a negative impact on return on assets. It indicates that increase in leverage ratio leads to decrease in return on assets. Further, the study showed that assets tangibility has a positive impact on return on assets. It means that higher the assets tangibility, lower would be the return on assets. In addition, firm size has a positive impact on return on assets and earnings per share. It indicates that increase in firm size leads to increase in return on assets and earnings per share. Moreover, liquidity ratio has a negative impact on return on assets and earnings per share. It shows that higher the liquidity ratio, lower would be the return on assets and earnings per share. However, total debt ratio has a negative impact on earnings per share. It means that higher the total debt to total equity ratio, lower would be the earnings per share. Similarly, total equity to total assets ratio has a negative impact on earnings per share. It means that increase in total equity to total assets ratio leads to decrease in earnings per share.